Randomized clinical trial on the effect of intermittent vibrational force application during orthodontic treatment with aligners on RANKL and OPG concentrations in crevicular fluid - Alicia Pérez Idarraga; Fara Yeste Ojeda; Leire Virto Ruiz; Miguel Lacasa Litner; Alberto Cacho Casado; Conchita Martin (Wiley, 2023)
Abstract Application of intermittent forces by vibration is proposed as an easy‐to‐use accelerator of dental movement. The purpose of this study was to determine the effect of intermittent vibrational force application during orthodontic aligner treatment on receptor activator of nuclear factor‐kappa B ligand (RANKL) and osteoprotegerin (OPG) concentrations in crevicular fluid as markers of bone remodeling. This three‐arm parallel randomized clinical trial included 45 candidates for malocclusion treatment with aligners, randomly assigned to: Group A (vibrational forces from onset of treatment); Group B (vibrational forces at 6 weeks after treatment onset); or Group C (no vibration). The frequency of aligner adjustment also differed among groups. At different time points, a paper tip was used to draw crevicular fluid samples from a moving lower incisor for RANKL and OPG analysis using ELISA kits. Mixed‐model ANOVA found no significant differences in RANKL (A: p = 0.31, B: p = 0.8, C: p = 0.49) or OPG (A: p = 0.24, B: p = 0.58, C: p = 0.59) over time in any group or as a function of the application/non‐application of vibration or the frequency of aligner adjustments. Application of this accelerator device did not significantly affect bone remodeling in patients undergoing orthodontic treatment with aligners. However, a nonsignificant improvement in biomarker concentrations was observed when aligners were changed every 7 days and vibration was also applied. Further research is warranted to establish protocols for the application of vibration and the timing of aligner adjustments.